Safety of Ticagrelor Compared to Clopidogrel after Prehospital Initiation of Treatment - Bergmeijer, Thomas O.; van Oevelen, Mathijs; Janssen, Paul W. A.; Godschalk, Thea C.; Lichtveld, Robert A.; Kelder, Johannes C.; Voskuil, Michiel; Mosterd, Arend; Montalescot, Gilles; ten Berg, Jurriën M. (TH Open, 2018)
Objectives The objective of this registry was to study the safety of prehospital initiation of ticagrelor compared with clopidogrel.Background Ticagrelor has replaced clopidogrel in many hospitals as the routinely used antiplatelet drug in patients with ST-segment elevation myocardial infarction (STEMI). Nevertheless, in the PLATelet inhibition and patient Outcomes (PLATO) trial, ticagrelor was associated with an increase in non-CABG (non–coronary artery bypass grafting)-related major bleeding. Data comparing the safety of ticagrelor and clopidogrel after prehospital initiation of treatment are not available.Methods A retrospective, multicenter registry was performed. Selection criteria were the administration of a prehospital loading dose of ticagrelor or clopidogrel according to the ambulance STEMI treatment protocol and the presentation to a percutaneous coronary intervention–capable hospital in our region between January 2011 and December 2012. Follow-up was performed using the electronic patient files for the time period between the antiplatelet loading dose and hospital discharge. The data were analyzed using a primary bleeding end point (any bleeding) and a secondary thrombotic end point (all-cause mortality, spontaneous myocardial infarction, definite stent thrombosis, stroke, or transient ischemic attack).Results Data of 304 clopidogrel-treated and 309 ticagrelor-treated patients were available for analysis. No significant difference in bleeding rate was observed between both groups, using univariate (17.8 vs. 20.1%; p = 0.47; odds ratio, 1.16 [95% confidence interval, 0.78–1.74]) and multivariate (p = 0.42) analysis. Also for the secondary thrombotic end point (6.3 vs. 4.9%, p = 0.45), no significant differences were observed.Conclusion In this real-world registry, no significant differences in bleeding or thrombotic event rate were found between ticagrelor and clopidogrel after prehospital initiation of treatment.
Keywords: myocardial infarction; ticagrelor; clopidogrel; prehospital emergency care; hemorrhage